Successful implantation of S‐ICD using the intermuscular two‐incision technique in a patient with severe pectus excavatum. Issue 11 (25th November 2021) - Guarracini, Fabrizio; Marini, Massimiliano; Strazzanti, Mattia; Bonmassari, Roberto; Guarracini, Stefano; Di Mauro, Michele; Droghetti, Andrea
Abstract: A patient with severe pectus excavatum, dilated ischemic heart disease, and indication for defibrillator implantation for primary prevention of sudden death underwent successful ultrasound‐guided serratus anterior plane block and parasternal block with intermuscular two‐incision technique implantation with no complications. At follow‐up, all the parameters resulted stable with excellent signal sensing. Abstract : In case of severe pectus excavatum, an ultrasound‐guided serratus anterior plane block and parasternal block with intermuscular two‐incision technique implantation can be useful.